Tamoxifen with radiotherapy compared with Tamoxifen alone in elderly women with early-stage breast cancer treated with breast conserving surgery: A systematic review and meta-analysis. Issue 1 (April 2017) - Chesney, Tyler R.; Yin, Jennifer Xin; Rajaee, Nikoo; Tricco, Andrea C.; Fyles, Anthony W.; Acuna, Sergio A.; Scheer, Adena S.
Abstract: Background: Our aim was to assess the effect of adjuvant radiotherapy on recurrence and survival for elderly women (≥70) with early-stage hormone receptor-positive breast cancer treated with breast conserving surgery (BCS) and Tamoxifen. Materials and methods: MEDLINE, EMBASE, and Evidence-Based Medicine Reviews were systematically searched through August 12, 2016 for randomized controlled trials (RCTs) comparing radiotherapy to no radiotherapy and presenting outcomes for women ≥70 years. Two investigators screened citations, abstracted results, and appraised studies using Cochrane Risk of Bias tool. Pooled risk ratios (RR) for breast, axillary, and distant recurrence, and overall survival were determined using weights from fixed-effects models. Results: Four RCTs with low risk of bias were identified (2387 elderly women). Tamoxifen plus radiotherapy reduced breast recurrence compared to Tamoxifen alone from 60 to 10 (95% CI 6–20) per 1000 patients at 5 years (RR 0.18, 95% CI 0.10–0.34; 4 trials, 2387 patients). This effect was maintained at 10 years (RR 0.27, 95% CI 0.13–0.54; 2 trials, 891 patients). Radiotherapy minimally reduced axillary recurrence from 12 to 3 (95% CI 1–10) per 1000 at 5 years (RR 0.28, 95% CI 0.10–0.81; 3 trials, 2287 patients). Radiotherapy did not affect distant recurrence (RR 1.49, 95% CI 0.87–2.54; 3 trials, 2287 patients) or overall survival (RR 0.98, 95% CI 0.79–1.22; 3 trials, 2287 patients). Conclusion: For elderly women (≥70), radiotherapy reduces the risk of breast and axillary recurrence, but does not impact distant recurrence or overall survival in early-stage breast cancer treated with BCS and Tamoxifen. The value of this risk reduction must be weighed by women and their physicians when considering the omission of adjuvant radiotherapy.